Occupational Exposure to Fine Particulate Matter (PM(4) and PM(2.5)) during Hand-Made Cookware Operation: Personal, Indoor and Outdoor Levels - Shezi, Busisiwe (Int J Environ Res Public Health, 2020)
(1) Exposure of informal artisanal cookware makers to fine particles has not yet been characterized. The aim of this study was to characterize occupational exposure to fine particulate matter (PM(4) and PM(2.5)) levels and fine particulate matter (PM(2.5)) elemental components; (2) Artisanal cookware makers were recruited from five cookware making sites. Exposure to fine particulate matter was measured for 17 male participants. SidePak personal aerosol monitors (AM520) were used to measure personal exposure to PM(4), while a DustTrak monitor and an E-sampler were used to assess indoor and outdoor PM(2.5) levels, respectively. A questionnaire was administered to capture information on demographic characteristics. The chemical characterization of indoor and outdoor PM(2.5) filter mass was conducted using Wavelength Dispersive X-ray Fluorescence. Time series record of 15-min averages for indoor and outdoor PM(2.5) levels were assessed; (3) The median (range) was 124 µg/m(3) (23−100,000), 64 µg/m(3) (1−6097) and 12 µg/m(3) (4−1178), respectively, for personal PM(4), indoor and outdoor PM(2.5). The highest levels for many of the elemental components of PM(2.5) were found in the outdoor PM(2.5) filter mass and (4). The information generated during this study may assist in extending occupational health and safety strategies to artisanal cookware makers and developing targeted prevention initiatives.